Comparative Genomics Reveals Specific Genetic Architectures in Nicotine Metabolism of Pseudomonas sp. JY-Q - Li, Jun; Qian, Shulan; Xiong, Lie; Zhu, Chengyun; Shu, Ming; Wang, Jie; Jiao, Yang; He, Houlong; Zhang, Fuming; Linhardt, Robert J.; Zhong, Weihong (Frontiers in Microbiology, 2017)
Microbial degradation of nicotine is an important process to control nicotine residues in the aqueous environment. In this study, a high active nicotine degradation strain named Pseudomonas sp. JY-Q was isolated from tobacco waste extract. This strain could completely degrade 5.0 g l−1 nicotine in 24 h under optimal culture conditions, and it showed some tolerance even at higher concentrations (10.0 g l−1) of nicotine. The complete genome of JY-Q was sequenced to understand the mechanism by which JY-Q could degrade nicotine and tolerate such high nicotine concentrations. Comparative genomic analysis indicated that JY-Q degrades nicotine through putative novel mechanisms. Two candidate gene cluster duplications located separately at distant loci were predicted to be responsible for nicotine degradation. These two nicotine (Nic) degradation-related loci (AA098_21325 - AA098_21340, AA098_03885 - AA098_03900) exhibit nearly completely consistent gene organization and component synteny. The nicotinic acid (NA) degradation gene cluster (AA098_17770 - AA098_17790) and Nic-like clusters were both predicted to be flanked by mobile genetic elements. Furthermore, we analyzed the regions of genomic plasticity in the JY-Q strain and found a dynamic genome carrying a type VI secretion system (T6SS) that promotes nicotine metabolism and tolerance based on transcriptomics and used in silico methods to identify the T6SS effector protein. Thus, a novel nicotine degradation mechanism was elucidated for Pseudomonas sp. JY-Q, suggesting its potential application in the bioremediation of nicotine-contaminated environments, such as tobacco waste extracts.